Communication Between Anaesthesia Providers for Clinical and Professional Purposes: A Scoping Review - Hilary Edgcombe; Gatwiri Murithi; Mudola Manyano; Sophie Dunin; Neal Thurley; Helen Higham; Mike English; Claire Blacklock (Anesthesiology Research and Practice)
Conclusion: Communication between anaesthesia providers affects all aspects of their practice and has implications for both patient outcomes and workforce capacity. More research is necessary to understand how the availability of communication as a resource affects patient care and health worker well-being, particularly in low- and middle-income contexts and among nonphysician anaesthesia providers.